STATE LOSSES DUE TO CORRUPTION - Puspitasari, Feny; Siregar, Vivi Arfiani; Darmiwati, Darmiwati (International Journal of Multidisciplinary Research and Literature, 2024)
Corruption is a criminal act in Indonesia which is still classified as a very high crime and no way has been found to overcome it. So the author is interested in conducting research using library research methods by studying and examining various sources such as books related to state losses due to corruption. And the conclusions from writing this journal are (1) corruption is deviant behavior carried out by someone with the aim of gaining financial gain and generally the term corruption is used for someone who likes to take money for personal gain, (2) carrying out corruption of course results in losses the state becomes quite large, state financial losses are a shortage of money, securities and also real and definite amounts of goods as a result of unlawful acts whether intentional or unintentional, (3) the efforts made in the process of returning state financial losses are by through three channels including criminal, civil and administrative or political channels, (4) and the role of the Attorney General's office in recovering state financial losses is by carrying out investigations, prosecutions and also executions in criminal cases, where the execution here is as executor in implementing court decisions